Consciência negra, justiça ambiental e sustentabilidade - Lamin-Guedes, Valdir (Sustainability in Debate, 2013)
One of the goals of working with Black consciousness is showing how Brazil is marked by racial differentiation and discrimination, once the issue of racism has been almost permanently denied, both inside and outside country. We are all invited to think about the inclusion of Blacks in the Brazilian society, as well as about the environmental injustice they are subject to. As a population less endowed with financial, political and/or informational resources, Black people experience a disproportionate imposition to environmental risks. The quest for a sustainable development that includes an economic, social and ecological balance involves the search for greater environmental justice.